Islamic Religious Education Learning Design by Learning Management System (LMS) Assessment of the PAI KKG Group In The Covid-19 Pandemic Era - Husniyah, Nur Iftitahul; Purwanto, Purwanto (EDUCATIO : Journal of Education, 2021)
The world is changing with the Covid-19 pandemic, changes occur in all life, including in the education sector. The most visible consequence of the shift in the world of education on the sidelines of the Covid-19 pandemic is the evolution of studying education. Schools must be mature in carrying out distance learning as an alternative to face-to-face learning. The distance learning system has characteristic provocations that inevitably have to be implemented. Learning design is a procedure and the implementation of learning as a whole. This includes learning objectives, learning methods and learning evaluation. In addition, to facilitate the transfer of knowledge from a teacher to students effectively, an appropriate media is needed. Because learning design is a strategy to apply technological media that has been prepared according to learning needs. Therefore, a learning implementation plan is needed that is needed and in accordance with existing conditions in order to realize learning goals. Teacher productivity is very much needed, especially PAI teachers in this Covid-19 pandemic era, so they must stop using simple or standard techniques. The Learning Management System is an alternative solution for distance learning in this pandemic era. Learning Management System (LMS) is a software application or software for online activities, in which there is training content or also called software for planning, electronic learning programs (e-learning programs), and virtual classrooms, and instructor programs. the guided, delivery, and management of learning activities within an organization, including 'online'. LMS combines traditional courses with digital media or interactive tools such as online and offline tutoring, virtual live sessions and discussion forums.